MEDICATION BELIEFS AMONG PATIENTS WITH HEART FAILURE: CONCEPTS AND IMPLICATIONS FOR NURSES - Chaiponbal, Supattra; Pongtriang, Sasikan; Changto, Jutatip; Chintapanyakun, Teepatad (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
The beliefs about medication for patients with heart failure are a behavior of patients that shows the relationship between medication adherence and advice received from medical personnel. According to Horn’s concept, beliefs about medication consisted of 2 main beliefs: 1) Specific beliefs, consisting of specific – necessity beliefs in the perception of the medication, which are beliefs about the necessity and effectiveness of medication, and specific – concern beliefs in the medication adherence, which are concerns about the harmful effects of medication. 2) General beliefs, consisting of general beliefs in overuse of medication, which are beliefs that medications are generally overused according to the doctor’s treatment plan, and general harm beliefs in the dangers of medication adherence. Medication adherence for patients with heart failure is considered important because it helps control symptoms and signs, and the severity of disease. If patients have beliefs about medication adherence along with self-regulation of health and illness, they will be able to take care of themselves and have a good quality of life. Therefore, the important role of nurses is to promote knowledge about the disease, the necessity of taking medication regularly, and appropriate self-care behaviors.